Methane production increases with warming and carbon additions to incubated sediments from a semiarid reservoir. Issue 1 (2nd January 2018) - Rodriguez, Maricela; Gonsiorczyk, Thomas; Casper, Peter
Abstract: Methane production (MP) in aquatic systems is positively related to temperature and trophic state. Global warming and eutrophication are predicted to potentiate MP in freshwater reservoirs. The simultaneous impact of rising temperature and carbon and nutrient additions on MP were examined in a tropical semiarid hydropower reservoir. Sediments cores from 3 locations (profundal, littoral, and intermediate) with differing water depth were sectioned and slurries incubated at 20, 30, and 40 °C with or without additions of carbon, nitrogen, or phosphorus, or all combined. Maximal MP (4.2 μmol g DW −1 d −1 ), occurred under carbon addition, and mean MP was about twice as high than in the control, independent of temperature. The effect of carbon additions manifested differently at the 3 locations, with enhancement of MP greater in upper sediment layers of the profundal location and in deeper layers (4–8 cm) of littoral and intermediate locations. Without carbon addition, MP was slower and positive effects of warming were more frequent, especially in littoral. These results suggest that the combined effect of warming and land use changes, principally on carbon loads, will increase the MP and methane emissions potential in this semiarid reservoir. Differences in effects are linked to location in the reservoir.